2014
DOI: 10.1111/imm.12251
|View full text |Cite
|
Sign up to set email alerts
|

The identification and developmental requirements of colonic CD169+ macrophages

Abstract: SummaryCD169-positive macrophages in the marginal zone of the spleen and subcapsular sinus of lymph nodes play an important role as gatekeepers, strategically located to capture pathogens. Here we identified a population of CD169-positive macrophages in the colon and investigated which factors influenced their development. Murine colonic CD115 + F4/80 lo CD11c lo macrophages expressing CD169 were present in the lamina propria, mainly surrounding the crypts. In spite of the high levels of bacterial flora in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 56 publications
1
39
1
Order By: Relevance
“…Mφs are found in a number of locations within the mucosa itself, ranging from immediately next to the basement membrane underlying the epithelium to the central core of the LP, and at different positions along the villus-crypt axis (Figure 2A). A specific population expressing CD169 is found near the crypt base, close to the submucosa and these may have distinct functions and developmental requirements 51,52 . Substantial numbers of mφs are also found in the external muscularis layer of the intestine ( Figure 1A).…”
Section: Ii) Specialised Macrophage Microenvironments Within the Intementioning
confidence: 99%
See 1 more Smart Citation
“…Mφs are found in a number of locations within the mucosa itself, ranging from immediately next to the basement membrane underlying the epithelium to the central core of the LP, and at different positions along the villus-crypt axis (Figure 2A). A specific population expressing CD169 is found near the crypt base, close to the submucosa and these may have distinct functions and developmental requirements 51,52 . Substantial numbers of mφs are also found in the external muscularis layer of the intestine ( Figure 1A).…”
Section: Ii) Specialised Macrophage Microenvironments Within the Intementioning
confidence: 99%
“…Although mature resident mφs do not become proinflammatory during experimental colitis induced by chemicals or T cells 14,16,18 , this can occur under conditions when inflammation occurs in the absence of IL10 mediated control of mφ activity 21,128 . One population of resident mφs that may contribute directly to inflammation is that expressing CD169, which recruits monocyte neutrophils via production of CCL8 51,52 . Furthermore, muscularis mφs play important roles in postoperative paralytic ileus by producing nitric oxide in response to local trauma, leading to activation of neighbouring neurons 54 .…”
Section: A) Intestinal Macrophagesmentioning
confidence: 99%
“…13 Finally, CD169 + macrophages have also been described in the colon, their differentiation in the steady-state dependent on Vitamin A, and during intestinal inflammation secrete CCL8 to recruit inflammatory monocytes. 14,15 Resident intestinal MPs are thought to play an essential role in killing invading microbes, clearing dead and dying cells, control of intestinal inflammation, and contributing to wound healing and epithelial repair, 16,17 and they are highly phagocytic and bactericidal cells that respond to TLR ligands with the production of IL-10, and other anti-inflammatory, but low levels of inflammatory cytokines, 5,8,[18][19][20] and also have been reported to be important in the expansion or survival of regulatory T cells within the lamina propria through their production of IL-10 during steady state and colitis. 21,22 Several tissue-specific factors affecting intestinal MP identity and function have been described, including retinoic acid, microbial metabolites, TGFβ, and IL-10, however, other influences on intestinal MP phenotype are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphotoxin signaling is critical for CD169 ϩ cell development in spleen and lymph node tissues (32,38,39,41). Moreover, it has been shown that lymphotoxins are derived from B cells, which are important for maintenance of CD169 ϩ cells (29,39).…”
Section: Baffr Deficiency Results In Reduced B Cell-mediated Maintenamentioning
confidence: 99%
“…6A). These data suggest that impaired B cell numbers in Baffr Ϫ/Ϫ mice may contribute to insufficient lymphotoxin expression to maintain normal levels of CD169 ϩ cells (29,38,41,42). To investigate the role of lymphotoxin beta during enforced viral replication, we infected Ltb fl/fl ϫ CD19-Cre ϩ animals and compared them to their corresponding controls.…”
Section: Baffr Deficiency Results In Reduced B Cell-mediated Maintenamentioning
confidence: 99%